PENGARUH KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN, TERHADAP PRESTASI KERJA GURU ILMU PENGETAHUAN ALAM SEKOLAH MENENGAH PERTAMA NEGERI SE KOTA MAGELANG (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The purpose of the study was to determine the influence of leadership, motivation, and environment to work performance of the Science teachers in Magelang City both jointly and part by part.The population of this study were all Science teachers of junior high schools in Magelang City in 2014/2015 academic year, amounting to 60 teachers by census method. Date was collected by a questionnaire. The data was analized using the formula of multiple regretion and partial correlation coefficient.The results of multiple regretion  test shows that headmaster’s leadership, motivation, and work environment variables jointly have possitive effect on the teacher’s work permormance in the amount of 65.381%. This figures shows that 65.619% of teacher’s work performance is determined by three variables, meanwhile 24.619% of it is determined by other variables. Part by part, headmaster’ leadership variable gives effective contribution of 46.24%, motivation variable gives effective contribution of 47.26%, and work environment variable gives effective contribution of 0.7% , it means the better leadership ,motivation and work environment,the better work performance of science teachers. Meanwhile, the relative contribution of headmaster,  leadership variable is 49.1%,  the relative contribution of motivation variable is 50.2%,  and the relative contribution of work environment variable is 0.7%  suruh mengartikan spy orang awam mengerti.